Resident and Non-resident Father Involvement, Coparenting, and the Development of Children’s Self-Regulation Among Families Facing Economic Hardship - Altenburger, Lauren E. (Frontiers in Psychology, 2022)
Self-regulation, or the ability to effectively manage emotions and behavior, is a critical skill to develop in early childhood. Children living in a context of economic hardship are at an increased risk for developing self-regulation difficulties. However, few studies have comprehensively examined how multiple aspects of the caregiving environment, including fathers’ parenting and coparenting quality, may contribute to child self-regulation. Thus, this study applied a family systems perspective to examine whether coparenting and resident and non-resident fathers’ reports of parenting quantity and quality were associated with observations of children’s self-regulation. Participants were drawn from the Embedded Developmental Study (n = 257) of the Three-City Study, a longitudinal study of children and families facing economic hardship. At Wave 1, when children were 2–4 years old, reports of parenting (i.e., quantity and quality) and coparenting (i.e., support) were obtained. At Wave 2, when children were 3–6 years old, children participated in a snack delay and gift wrap task, which assessed their self-regulation. Multi-group path analyses indicated that resident fathers’ harsh parenting at Wave 1 predicted decreased levels of self-regulation at Wave 2. Non-resident fathers’ reported hours of involvement at Wave 1 predicted greater levels of self-regulation at Wave 2. Additionally, supportive coparenting among families with a non-resident father predicted greater self-regulation. Supportive coparenting was not associated with child self-regulation in families with a resident father. The implications for research focused on facilitating positive father–child relationships in diverse family contexts are discussed.